The Origin and Correlated Evolution of Symbiosis and Coloniality in Scleractinian Corals - Campoy, Ana Navarro; Addamo, Anna Maria; Machordom, Annie; Meade, Andrew; Rivadeneira, Marcelo M.; Hernández, Cristián E.; Venditti, Chris (Frontiers in Marine Science, 2020)
Symbiosis and coloniality are ecologically important traits for corals of the order Scleractinia. Symbiotic (zooxanthellate) species are highly successful in shallow waters of tropical and subtropical seas and most of them are colonial. On the other hand, azooxanthellate species present wide distribution ranges and expand to the deep-sea at more than 6,000 m depth. These are mostly solitary, with only few species colonial that form extensive deep reefs. Each ecologically distinctive group encompasses half of the biodiversity of the order and they are not grouped into differentiated monophyletic clades. Paleontologists and evolutionary biologists have debated for decades whether modern scleractinian corals have evolved from symbiotic or colonial ancestors and how these traits have evolved and being involved in the diversification process in corals. Previous comparative analyses throw evidence in favor of coevolution of these characters and toward repetitive loss of symbiosis and coloniality. Nevertheless, the discovery of the origin of the group deep in the Paleozoic, with a deep divergent clade composed of only azooxanthellate corals has questioned these findings. With this work, we disentangle the patterns in the evolution of symbiosis and coloniality, testing if they are correlated and if they follow a gradual or episodic mode of evolution. For this end, we first obtain the most complete time-calibrated phylogenetic tree for the order Scleractinia, including new sequences of never-before sampled species and genera. These novel sequences contribute to palliate the current molecular subsampling on azooxanthellate species. Incorporating phylogenetic uncertainty, we obtained strong evidence in favor of a reversible-jump continuous time Markov model of correlated and episodic evolution. This model led to the inference of an azooxanthellate and solitary most recent ancestor of scleractinians. Transition rates between the four different combinations of the two traits showed that while coloniality is gained and lost multiple times, symbiosis first appears around 282 Ma and is never lost. Also, coloniality seems to have appeared before symbiosis in azooxanthellate lineages. Thus, azooxanthellate corals, and especially colonial lineages, have been acting as a source of biodiversity for shallow zooxanthellate coral communities, highlighting the uniqueness of shallow and deep species and need of preserve them.